The hiding place [compact disc, unabridged] - Ten Boom, Corrie (Blackstone Audio Books, 1993)
This is the story of how Corrie and her family became leaders in the Dutch Underground, hiding Jewish people in a specially built room in their house and aiding their escape from the Nazis.